Synthesis and Antibacterial Activity of Some Substituted Isoxazolines and Isothiazolines - Naik, V.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Some substituted isoxazolines and isothiazolines were synthesized from chalcones. These varied products have been characterized by elemental analysis and spectral studies and tested for antibacterial activities against S. aureus and E. coli.